TRACE METAL CONCENTRATION AND HUMAN HEALTH RISK ASSESSMENT IN DISTILLED ALCOHOLIC BEVERAGES IN ROMANIA - BORA, Florin Dumitru; CĂLUGĂR, Anamaria; BUNEA, Claudiu Ioan; PETRESCU MAG, Ioan-Valentin; CIMPOIU, Claudia; FILIMON, Vasile Răzvan (Studia Universitatis Babeș-Bolyai Chemia, 2019)
The concentration of 12 metals (Mg, Ca, K, M, Fe, Co, Ni, Cr, Cu, Pb, Cd, and Zn) in 14 classes of alcoholic beverages were determined by ICP-MS after HNO3/H2O2 digestion. The mean concentration of metals (µg/mL) in these alcoholic beverages varied in the ranges 0.26-15.43, 0.94-234.43, 0.56-278.02, 0.02-2.69, 0.18-2.64, 0.03-0.13, 0.03-0.13, 0.02-0.29, 0.04-2.51, 0.03-0.30, 0.02-0.04, and 0.13-0.88 for Mg, Ca, K, Mn, Fe, Co, Ni, Cr, Cu, Pb, Cd, and Zn respectively. The concentration of metals found in these particular alcoholic beverages was below the International Statutory Limits for metals in alcoholic beverages. The estimated daily intake of the metals based on a per capita consumption of 14.4 L per annum pure alcohol was lower than the tolerable daily intake of each metal. The individual and combined target hazard quotients of the metals were <1, indicating no long-term health concerns from the consumption of these alcoholic beverages based on their metal content alone.